(untitled) (Journal of Global Arts Studies, 2024)
Background: The Korean KBS Dahe planned the documentary "Chinese Mainland", as the first Korean documentary on the subject of Chinese Mainland shot on the spot in Chinese Mainland, which has preserved a large number of valuable video data of China in the 1980s, and has made a positive contribution to promoting the establishment of diplomatic relations between China and the Republic of Korea to enhance the Korean people’s understanding of the Chinese Mainland. It can be regarded as a leading role in the establishment of diplomatic relations between China and the Republic of Korea. It is of great significance, extremely rare, and immortal enough. Unfortunately, the documentary has not received much attention and research from the academic circles of China and South Korea, and it has not gained much popularity and influence in the public and society, which is extremely disproportionate to its status and significance. Objective: This article adopts the research method of mutual verification between literature and history to explore the unique status and significance of this significant documentary, as well as the unavoidable defects and regrets. Methods: The original intention and motivation of writing this article is to draw attention and attention from the academic circles of China and South Korea to this important documentary, and to present this article as a tribute to the 30th anniversary of the establishment of diplomatic relations between China and South Korea. Results: The most direct significance of "Chinese Mainland" is that it has preserved a large number of precious video data of China in the 1980s. The indirect significance is that it has made positive contributions to promoting the establishment of diplomatic relations between China and the Republic of Korea, and has played a leading role in the establishment of diplomatic relations between China and the Republic of Korea. However, the documentary Chinese Mainland also has obvious and unavoidable defects. Nevertheless, the flaws do not conceal the merits, and it will not affect its existence as an excellent documentary. Conclusion: The author summarizes the significance and characteristics of the Korean KBS Dahe planning documentary "Chinese Mainland" in combination with the original intention and motivation of this writing into 15 words, namely, the main title of this article: forerunner of establishing diplomatic relations, late attention, and immortal significance.